A sensitivities based CoVaR approach to asset commonality and its application to SSM banks - Leonardo Del Vecchio; Carla Giglio; Frances Shaw; Guido Spanò; Giuseppe Cappelletti (European Central Bank (ECB), 2022)
One important source of systemic risk can arise from asset commonality among financial institutions. This indirect interconnection may occur when financial institutions invest in similar or correlated assets and it is also described as overlapping portfolios. In this paper, we propose a new methodology for identifying and assessing banking sector systemic risk stemming from asset commonality in the spirit of CoVaR as defined by Adrian and Brunnermeier (2016). Based on granular information, we compute bank portfolio sensitivities to a large number of risk factors (e.g. interest rates, equity prices, credit spreads, exchange rates) and then compute the gains and losses under a large number of historical scenarios and the associated ∆ CoVaR. The novel indicator proves to be consistent with other indicators of systemic importance, yet it has a more transparent foundation in terms of the source of systemic risk, which can contribute to effective micro and macroprudential supervision.
Keywords: C58; E32; G01; G12; G18; G20; G32; 330; Systemic risk; Overlapping portfolios; Financial networks; Financial regulation; CoVaR